Studying the changes in the mechanical properties of neutron-irradiated chromium-nickel steels using the “Shear Punch” method - Maksimkin, О.P.; Ruban, S.V.; Nurgaly, Y.Y.; Short, M.P. (Вопросы атомной науки и техники, 2019)
Obtaining mechanical properties of neutron irradiated structural materials is made difficult by the high radioactivity of typical specimen sizes. Developing new mechanical tests which obtain the same properties with far smaller specimen sizes would significantly enhance the speed and safety of performing such tests. In this study, we demonstrate the correspondence in mechanical properties between standard, uniaxial tensile testing and a new “Shear Punch” method, involving the shear-based removal of a small (1 mm) disc of material. Two types of steel, 12Cr18Ni9 and 08Cr16Ni11М3, were irradiated with fast neutrons in the BN-350 reactor up to 23 dpa and shear punch tested between 20…300 °C. Excellent correspondence was found between the 0.2% shear and uniaxial tensile yield stresses, validating this technique as a way to obtain the same mechanical properties with greatly reduced sample size.